Archival materials as historical resources about deported Latvian citizens in 1941, 1949 an in other periods. - Bambals, Ainars (Genocidas ir rezistencija, 2008)
This article is devoted to the scientific study of archival documents in the personal files of exiled Latvian citizens as a source of history. This topic may include broader themes by various authors, explored ‘on the basis of archival documents of the Soviet repressive institutions of the Latvian SSR as a historical source’. These documents reveal how the deportation process was organised and which people were deported.